2005
DOI: 10.1021/ja042207o
|View full text |Cite
|
Sign up to set email alerts
|

From CO Oxidation to CO2 Activation:  An Unexpected Catalytic Activity of Polymer-Supported Nanogold

Abstract: A simple, clean, safe, and reproducible catalyst system, polymer-supported nanogold, was successfully developed for the fixation of CO2 to cyclic carbonate and for the carbonylation of amines to disubstituted ureas with unprecedented catalytic activity (TOF > 50 000 mol/mol/h and TOFP approximately 3000 mol/mol/h, respectively). To the best of our knowledge, it was the first to report that nanogold catalysts have exclusive catalytic activity for activation of carbon dioxide, and that the catalytic activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(98 citation statements)
references
References 35 publications
1
95
0
2
Order By: Relevance
“…Their traditional synthesis required unsafe chemicals such as phosgene or carbon oxide and Au or Pt catalysts [35][36][37][38]. In recent years the direct synthesis of substituted ureas has been accomplished with the non toxic and cheap carbon dioxide in the presence of different catalysts and dehydrating agents to increase the yield of reaction [39][40][41][42]. Ionic liquids in conjunction with a base (CsOH) or transition metal (Fe, Co, Ni, Cu, Zn) acetates were also employed as reaction medium and catalysts to obtain 1,3-disubstituted ureas in good yield [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Their traditional synthesis required unsafe chemicals such as phosgene or carbon oxide and Au or Pt catalysts [35][36][37][38]. In recent years the direct synthesis of substituted ureas has been accomplished with the non toxic and cheap carbon dioxide in the presence of different catalysts and dehydrating agents to increase the yield of reaction [39][40][41][42]. Ionic liquids in conjunction with a base (CsOH) or transition metal (Fe, Co, Ni, Cu, Zn) acetates were also employed as reaction medium and catalysts to obtain 1,3-disubstituted ureas in good yield [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this mechanism, our group also carried out the related work, the disubstituted urea was firstly synthesized by polymer-immobilized nanogold catalyst and then alcoholysis over TiO 2 /SiO 2 catalyst. [61,62] In this way, the utilization of CO 2 as a carbonyl source for carbamate synthesis was realized via an efficient and environmentally friendly route to some extent.…”
Section: Methodsmentioning
confidence: 99%
“…Compound 1d exhibited the highest catalytic activity among all the catalysts. And the reactions were carried out at approximately 0.34 MPa of CO 2 pressure and [75][76][77][78][79][80][81][82][83][84][85] o C in the presence of 1 equiv of DMAP with TOFs (turnover frequency) ranging from 127-254 h -1 . Then, García and co-workers [11] successfully realized the separation of the catalysts from the reaction mixture and the reuse of the (salen)-metal catalyst in the coupling reaction of CO 2 and epoxides to provide cyclic carbonates.…”
Section: (Salen)cr For the Coupling Of Co 2 And Epoxidesmentioning
confidence: 99%
“…Sakakura and coworkers [83] reported cyclic carbonate synthesis from scCO 2 and epoxide over lanthanide oxychlo- [85] demonstrated that polymerimmobilized nano-gold catalysts had unprecedented catalytic activity for coupling epoxide and of carbon dioxide, with TOF > 50000 mol / mol / h for the synthesis of cyclic carbonate.…”
Section: Othersmentioning
confidence: 99%